KDM5B expression in cisplatin resistant neuroblastoma cell lines - Belhajova, Marie; Podhorska, Natalia; Vicha, Ales; Eckschlager, Tomas (Oncology letters, 2022)
Chemoresistance is a major problem in successful cancer therapy. Lysine-specific demethylase 5B (KDM5B), is a member of the KDM5 family of histone demethylases, whose dysregulation has been observed in numerous types of cancer and plays a role in drug tolerance. The present study examined KDM5B expression in high risk neuroblastoma cell lines. Its level was markedly reduced in cisplatin-resistant cells, UKF-NB-4CDDP, compared with parental sensitive cells UKF-NB-4. Moreover, KDM5B-silencing did not affect either viability nor the response to CDDP in resistant cells, and led to increase of proliferation and migration in CDDP resistant cells but not in sensitive ones. Compliant with these results, short interfering KDM5B transfection resulted in increased S phase in resistant cells. Overall, these findings suggested that KDM5B may be involved in the survival mechanisms of neuroblastoma cells, which makes KDM5B a promising factor for the prediction of sensitivity to CDDP that should therefore be considered for future research.
Keywords: neuroblastoma; cisplatin; lysine-specific demethylase 5B; histone methylation; chemoresistance